Analysis of A Two-Axis Solar Tracker System: Case Study - García-Quilachamin, Washington Xavier; Sánchez-Cano, Julieta Evangelina; Herrera-Tapia, Jorge; Velesaca-Zambrano, Edisson Javier (International Journal of Online and Biomedical Engineering (iJOE), 2021)
The environmental pollution that arose from the 20th century has led to the search for clean and renewable energies, so this research aims to determine the efficiency of a two-axis solar tracker system, through the analysis of the data obtained. In view of the fact that it remains perpendicular to the solar rays for a longer time, which automatically moves to the point where the radiation source is. Mathematical models were considered for this study based on parameters of time, voltage, solar radiation, temperature, ultraviolet radiation, inclination angles, and cardinal points, to which the panel was directed during the test days.  The efficiency given by the solar panel was obtained as 15.34% on average among monocrystalline silicon solar panels. It was concluded with the analysis of the most relevant data that are, the voltage, the solar radiation, and the angle of inclination to determine with these three parameters if the dual-axis tracker system had an excellent capture of solar radiation in the test days, in order to make the collection and production of solar energy more efficient.